The Nucleus “Agua” in the Phraseology of American Spanish - Luque, Rocío (Oltreoceano - Rivista sulle migrazioni, 2024)
The aim of this article is to analyse the phraseological units (PU) that have been created around the nucleus “water” in the different varieties of American Spanish in order to observe how this element, essential in human life, reflects the cultural universe, worldviews, beliefs, stereotypes and metaphorical competence of the linguistic communities involved. While the meaning of the referent will, on the one hand, facilitate the transparency of the phraseologisms examined, on the other hand, we will find constructions which are partially opaque in their meaning due to the projection of the image generated from a common name. At the same time, we will examine the existence of synonyms, geo-synonyms and antonyms among the PUs of the different varieties of American Spanish, as well as the polysemic constructions, variants, barbarisms and indigenisms present in them.